Biomass, Morphology, and Dynamics of the Fine Root System Across a 3,000-M Elevation Gradient on Mt. Kilimanjaro - Sierra Cornejo, Natalia; Hertel, Dietrich; Becker, Joscha N.; Hemp, Andreas; Leuschner, Christoph (Frontiers in Plant Science, 2020)
Fine roots (≤ 2 mm) consume a large proportion of photosynthates and thus play a key role in the global carbon cycle, but our knowledge about fine root biomass, production and turnover across environmental gradients is insufficient, especially in tropical ecosystems. Root system studies along elevation transects can produce valuable insights into root trait-environment relationships and may help to explore the evidence for a root economics spectrum (RES) that should represent a trait syndrome with a trade-off between resource acquisitive and conservative root traits. We studied fine root biomass, necromass, production and mean fine root lifespan (the inverse of fine root turnover) of woody plants in six natural tropical ecosystems (savanna, four tropical mountain forest types, tropical alpine heathland) on the southern slope of Mt. Kilimanjaro (Tanzania) between 900 and 4500 m a.s.l.. Fine root biomass and necromass showed a unimodal pattern along the slope with a peak in the moist upper montane forest (~2800 m), while fine root production varied little between savanna and upper montane forest to decrease towards the alpine zone. Root:shoot ratio (fine root biomass and production related to aboveground biomass) in the tropical montane forest increased exponentially with elevation, while it decreased with precipitation and soil nitrogen availability (decreasing soil C:N ratio). Mean fine root lifespan was lowest in the ecosystems with pronounced resource limitation (savanna at low elevation, alpine heathland at high elevation) and higher in the moist and cool forest belt (~1800-3700 m). The variation in root traits across the elevation gradient fits better with the concept of a multi-dimensional RES, as root tissue density and specific root length showed variable relations to each other, which does not agree with a simple trade-off between acquisitive and conservative root traits. In conclusion, despite large variation in fine root biomass, production and morphology among the different plant species and ecosystems, a general belowground shift in carbohydrate partitioning is evident from 900 to 4500 m a.s.l., suggesting that plant growth is increasingly limited by nutrient (probably N) shortage toward higher elevations.